Chapter L’idea di lavoro di Gino Giugni nello Statuto dei lavoratori - SPEZIALE, Valerio (Firenze University Press, 2025)
The essay analyses Gino Giugni’s idea of work in the Workers’ Statute (l n. 300/1970). Giugni, who played a fundamental role in preparing the Government Bill, believed that the Statute should rebalance the subordination of workers through the recognition of their rights of freedom in companies and the protection of workers’ dignity. In addition, the Statute, as a law supporting Trade Unions, should favour the presence of the Unions in workplaces, recognising them rights which could transform them in a collective counterpower. These «ideas regarding work» were introduced in the Statute, which, however, together with the Unions’ counterpower, also recognized to workers individual rights claimed before the judge, with a point of view not accepted by this author. However, in spite of these differences, Giugni subsequently always defended a law that even now is a fundamental regulation in Labour Law.